DIRECT SYNTHESIS OF STUB LOW-PASS FILTERS WITH CHEBYSHEV CHARACTERISTIC - Karpukov, L. М.; Korolkov, R. Y. (Radio Electronics, Computer Science, Control, 2013)
The method of synthesis of stub lowpass filters with Chebyshev characteristic that does not use filters prototypes is proposed. This method is used to solve the problem of synthesizing a lowpass filter with a symmetrical structure, being composed of quarter wavelength transmission lines and open-circuit stubs. In the process of solving this task are defined model elements of the filter structure. Composed filtering function to ensure equal characteristics. A procedure for the synthesis, starting with the choice of filter elements and ending with the determination of their impedances. A comparison of the results of synthesis of the proposed direct method and a method that uses the prototype filter, show the advantages of the proposed method.